Information security applications : 8th International Workshop, WISA 2007 Jeju Island, Korea, August 27-29, 2007 : revised selected papers - Sehun, Kim; Yung, Moti; Lee, Hyung-Woo (Lecture notes in computer science, 2008)
This book constitutes the refereed proceedings of the 8th International Workshop on Information Security Applications, WISA 2007, held in Jeju Island, Korea, August 27-29, 2007.The 27 revised full papers presented were carefully selected during two rounds of reviewing and improvement from 95 submissions. The papers are organized in topical sections on Public Key Crypto Applications, Biometrics/Information Hiding, Secure Hardware, Secure Systems, Wireless & Mobile Security, Application Security/Secure Systems, Access Control/DB Security, Smart Cards/Secure Systems and Anonymity & P2P Security.